Effect of Green Accounting, Intellectual Capital on Financial Performance, and Competitive Advantage as moderating variables - Choiriah, Siti; Lysandra, Shanti (Technium Social Sciences Journal, 2022)
This study empirically examines whether competitive advantage (CA) moderates Green Accounting, Intellectual Capital on Financial Performance. This research is a causal research with a quantitative descriptive approach with the object of research on manufacturing companies listed on the Indonesia Stock Exchange (IDX). The research data is secondary data obtained from financial reports and sustainability reports (SR) of manufacturing companies listed on the Indonesia Stock Exchange. The variables of this study consist of three independent variables and one dependent variable, namely green accounting, intellectual capital, competitive advantage and the dependent variable, namely financial performance. The results of the study state that green accounting has an effect on financial performance, intellectual capital has an effect on financial performance, while Competitive Advantage moderates the relationship between intellectual capital and financial performance but does not moderate the relationship between green accounting and financial performance.